Beckman Blood Cell Counter BBC-100
Based on the Coulter principle, the Beckman Blood Cell Counter quantifies and sizes particles suspended in a fluid, like blood cells. The instrument works by drawing liquid containing the particles through a channel, where each particle releases an electrical charge that is measured and counted. The Coulter principle was discovered by Wallace H Coulter in the late 1940s and patented in 1953. The Coulter counter was manufactured by Coulter Corporation until 1997, when the company was acquired by Beckman Instruments and became known as Beckman Coulter, Inc.
Keywords: Medical laboratory technology; Scientific apparatus and instruments; Blood cell count--Equipment and supplies; Flow cytometry; Beckman Instruments, Inc.